Estudo multicaso de práticas de implantação do método SMED - Pereira, Marcelo Alves (2010)
The improvement of the productivity in the production processes became a constant search of the companies. In that search, several tools, methods or techniques are to the disposition. Being taken in consideration that the productivity is just an end, they are necessary means to promote her. The method developed by Shigeo Shingo he intends to that, denominated SMED - Single Minute Exchange of Die, and that can be translated by fast change of tool in an type of minute, it proposes that the setups is accomplished in less than 10 minutes, possible time of being reached starting from the rationalization of the tasks of the operator and improvements accomplished in the machine. The implantation of the method SMED possesses low costs initially, needing much more initiatives relatively simple and of adoption of procedures of works equally simple and of easy understanding to the workers. This multiple case studies accomplished in three companies of different industrial segments, with the objective of understanding the practices adopted in the implantation of the method SMED, that respected your implantation formats they based originally on the works developed by Shigeo Shingo. The study identifies the reason of the companies in adopting the method and as they structured the implantation in function of your peculiarities and financial readiness. Central aspects, as the work route for implantation of the method, the workers' training, the reductions of time of setup and the form that the companies adopted to accompany and to control the method, they were appropriately described. The results demonstrate that the companies got to reduce significantly the hours used with setup, with won considerable made possible by the reduction of overtimes or work shifts, of the promotion of a significant improvement of the work areas and of the conditions of the workers' work, evidencing the different forms adopted to accompany and to control the acting of the method. It was still possible, starting from the acquired experience in the execution of this dissertation, to elaborate a route of eight stages with recommendations for the process of implantation of the method SMED.